Pengaruh blended learning terhadap motivasi belajar dan hasil belajar siswa di tingkat SMK - Sulihin B Sjukur (Jurnal Pendidikan Vokasi, 2012)
Penelitian ini bertujuan untuk: 1) mengetahui perbedaan motivasi belajar dan hasil belajar antara siswa yang diajarkan pembelajaran blended learning dibanding siswa yang diajarkan pembelajaran konvensional, 2) mengetahui peningkatan motivasi belajar dan hasil belajar siswa akibat penerapan pembelajaran blended learning. Jenis penelitian ini quasi experiment. Populasi penelitian adalah sebanyak 62 siswa dilakukan secara random assignment. Teknik pengumpulan data menggunakan tes tertulis dan angket. Data yang diperoleh dianalisis serta diuji dengan statistik parametrik uji F dan uji t. Hasilnya sebagai berikut. 1) Terdapat perbedaan motivasi belajar antara siswa yang diajar pembelajaran blended learning dibandingkan siswa yang diajar pembelajaran konvensional dengan nilai sig. 0,012 dengan rata-rata 4,74 dan terdapat perbedaan hasil belajar dengan nilai sig. 0,000 dengan rata-rata 13,39. 2) Ada peningkatan motivasi belajar siswa akibat penerapan pembelajaran blended learning dengan nilai sig. 0,000 rata-rata peningkatan 13,55 dan ada peningkatan hasil belajar siswa dengan nilai sig. 0,000 rata-rata peningkatan 38,23. THE EFFECTS OF BLENDED LEARNING ON THE LEARNING MOTIVATION AND ACHIEVEMENT STUDENTS LEVEL SMKAbstractThis research is aimed to: 1) find out the difference in learning motivation and learning achievement of the students taught using blended learning compared to those taught using conventional learning, 2) find out the improvement in learning motivation and learning achievement of the students due to blended learning application. The research type used is quasi-experiment research. The population of this research students which comprised of 62 students. To determine a random assignment. The data collection techniques used are written test and questionnaire. The data gathered was then analyzed and tested by using the F-test and t-test parametric statistics. The results are as follows. 1) There is a difference in learning motivation of the students taught using blended learning compared to those taught using conventional learning with the sig. 0.012 with the average 4.74 and there is a difference in learning achievement of the students with the sig 0.000 with the average 13.39. 2) there is an improvement in learning motivation of the students due to blended learning application with the sig. 0.000 with the average 13.55 and there is an improvement in learning achievement of the students with the sig. 0.000 with the average 38.23.